2017
DOI: 10.1111/aos.13487
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and metabolic comorbidities in open‐angle glaucoma with low‐ and high‐teen intraocular pressure: a cross‐sectional study from South Korea

Abstract: Various vascular and metabolic comorbidities were significantly associated with low-teen OAG, but not with high-teen OAG. These data support the hypothesis that vascular factors play a more significant role in the pathogenesis of OAG with low-teen baseline IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
47
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 62 publications
7
47
1
1
Order By: Relevance
“…Lee et al conducted a cross-sectional study in South Korea and found that patients with NTG had a significantly higher prevalence of hypertension, hyperlipidaemia, ischaemic heart disease and metabolic syndrome. 31 These findings are compatible with our findings in table 1 . Compared with patients with non-NTG, we also found that patients with NTG tended to be older and female predominant.…”
Section: Discussionsupporting
confidence: 93%
“…Lee et al conducted a cross-sectional study in South Korea and found that patients with NTG had a significantly higher prevalence of hypertension, hyperlipidaemia, ischaemic heart disease and metabolic syndrome. 31 These findings are compatible with our findings in table 1 . Compared with patients with non-NTG, we also found that patients with NTG tended to be older and female predominant.…”
Section: Discussionsupporting
confidence: 93%
“…Of these studies, 18 studies reported on the relationship between hyperlipidemia (hyperlipidemia or hypertriglyceridemia or hypercholesterolemia) and glaucoma, 7,8,32,34-39,44,45,47,48,50- 54 1 on blood highdensity lipoprotein-cholesterol (HDL-c) level and glaucoma, 55 1 on hyperlipidemia and OHT, 42 5 on blood triglyceride level and IOP, 9,10,33,43,46 2 on blood HDL-c level and IOP, 10,43 2 on total cholesterol level and IOP, 43,46 1 on low-density lipoprotein-cholesterol (LDL-C), 43 and 3 on hyperlipidemia and IOP. 40,41,49 When assessing the relationship between hyperlipidemia and glaucoma, four studies [34][35][36]39 reported on the association between both hypertriglyceridemia or hypercholesterolemia and glaucoma. We assumed that the hypercholesterolemia patients and the hypertriglyceridemia patients were the subjects of two separate studies.…”
Section: Literature Searchmentioning
confidence: 99%
“…A vascular aetiology has been hypothesized to play a critical role in glaucoma progression (Lee et al. ). The Leuven Eye Study conducted by Abegao Pinto et al.…”
Section: Physical Exercise and Ocular Perfusionmentioning
confidence: 99%
“…However, many patients suffer from glaucoma progression despite a normal IOP. A vascular aetiology has been hypothesized to play a critical role in glaucoma progression (Lee et al 2017). The Leuven Eye Study conducted by Abegao Pinto et al (2016) found that patients with glaucoma had lower retrobulbar velocities compared to the normal subjects.…”
Section: Physical Exercise and Ocular Perfusionmentioning
confidence: 99%